Diversity and Phylogenetic Position of Bothrostoma Stokes, 1887 (Ciliophora: Metopida), with Description of Four New Species - Méndez-Sánchez, Daniel; Pomahač, Ondřej; Rotterová, Johana; Bourland, William; Čepička, Ivan (Protist, 2022)
Bothrostoma is a genus of anaerobic ciliates in family Metopidae comprising four species, all described based solely on the morphology of living and fixed cells. Unlike other metopids, cells of Bothrostoma are not twisted anteriorly, have a flattened preoral dome, a very prominent sail-like paroral membrane, and an adoral zone of distinctive, very narrow, curved membranelles confined to a wide, non-spiraling peristome on the ventral side. We examined 20 populations of Bothrostoma from hypoxic freshwater sediments. We provide morphological characterization and 18S rRNA gene sequences of four new species, namely B. bimicronucleatum sp. nov., B. boreale sp. nov., B. kovalyovi sp. nov., and B. robustum sp. nov., as well as B. undulans (type species), B. nasutum, and B. ovale comb. nov. (original combination Metopus undulans var. ovalis Kahl, 1932). Except for B. nasutum, Bothrostoma species show low genetic variability among geographically distant populations. Intraspecific phenotypic variability might be driven by environmental conditions. In phylogenetic analyses, Bothrostoma is not closely related to Metopus sensu stricto and forms a moderately supported clade with Planometopus, here referred to as BoPl clade. The anterior axial torsion of the body, typical of other Metopidae, appears to have been lost in the last common ancestor of the BoPl clade.
Keywords: RNA ribozomální 18S; Metopus; Species Specificity; druhová specificita; sladká voda; 18S rRNA gene; Ciliophora; protargol impregnation; phylogeny; Phylogeny; Fresh Water; RNA, Ribosomal, 18S; Ciliates; anoxia; fylogeneze